A Political Theory of Government Debt and Deficits in a Neo-Ricardian Framework - Cukierman, Alex; Meltzer, Allan H. (American Economic Review, 1989)
Individuals differ in abilities. Some are bequest constrained even in a neo-Ricardian world. They vote taxes to issue bonds to be paid by taxes on future generations, thereby increasing current consumption, crowding-out capital, reducing wage rates, and increasing the interest rate. Therefore even unconstrained individuals are not indifferent to the size of government debt. Conditions conducive to larger debt and deficits are derived when each of the living generations determines current taxes, Social Security benefits and the national debt by majority rule.